Macrophage induced ERK-TGF-β1 signaling in MCF7 breast cancer cells result in reversible cancer stem cell plasticity and epithelial mesenchymal transition - Kundu, Priya; Shankar, Bhavani S. (Biochimica et biophysica acta. General subjects, 2022)
Breast cancer is a heterogenous disease composed of multiple clonal populations and the mechanism by which the tumor microenvironment induces cancer stem cell plasticity is not fully understood.BACKGROUNDBreast cancer is a heterogenous disease composed of multiple clonal populations and the mechanism by which the tumor microenvironment induces cancer stem cell plasticity is not fully understood.MCF7 breast cancer cells were treated with macrophage conditioned medium (MɸCM). PD98059 and SB431542 were used for ERK and TGF-βR inhibition respectively. Epithelial-mesenchymal transition (EMT) and cancer stem cell markers (CSC) were studied using qRT-PCR and flowcytometry. SCID mice were used for animal experiments.METHODSMCF7 breast cancer cells were treated with macrophage conditioned medium (MɸCM). PD98059 and SB431542 were used for ERK and TGF-βR inhibition respectively. Epithelial-mesenchymal transition (EMT) and cancer stem cell markers (CSC) were studied using qRT-PCR and flowcytometry. SCID mice were used for animal experiments.MɸCM- induced ERK/TGF-β1 signaling led to enrichment of CSC and EMT in MCF7 cells and mammospheres. These effects were abrogated by both MEK inhibitor PD98059 (TGF-β1 synthesis) and SB431542 (TGF-β1 signaling). The increase in CSC was both hybrid (ALDH1+) and mesenchymal (CD44+ CD24- cells). Increase in hybrid E/M state was at a single cell level as confirmed by the increase in both claudin-1 (E) and vimentin (M). This did not have any growth advantage in SCID mice and monitoring of CSC and EMT markers before and after growth in SCID mice indicated reversal of these markers in tumor cells recovered from mice. Removal of MɸCM and neutralization of TNF-α, IL-6 and IL-1β in MɸCM abrogated ERK phosphorylation, TGF-β and CSC enrichment indicating the requirement of continuous signaling for maintenance.RESULTSMɸCM- induced ERK/TGF-β1 signaling led to enrichment of CSC and EMT in MCF7 cells and mammospheres. These effects were abrogated by both MEK inhibitor PD98059 (TGF-β1 synthesis) and SB431542 (TGF-β1 signaling). The increase in CSC was both hybrid (ALDH1+) and mesenchymal (CD44+ CD24- cells). Increase in hybrid E/M state was at a single cell level as confirmed by the increase in both claudin-1 (E) and vimentin (M). This did not have any growth advantage in SCID mice and monitoring of CSC and EMT markers before and after growth in SCID mice indicated reversal of these markers in tumor cells recovered from mice. Removal of MɸCM and neutralization of TNF-α, IL-6 and IL-1β in MɸCM abrogated ERK phosphorylation, TGF-β and CSC enrichment indicating the requirement of continuous signaling for maintenance.ERK signaling plays an important role in MɸCM- induced EMT and CSC plasticity which is completely reversible upon withdrawal of signals.CONCLUSIONSERK signaling plays an important role in MɸCM- induced EMT and CSC plasticity which is completely reversible upon withdrawal of signals.Our experimental observations support the semi-independent nature of EMT-stemness connection which is very dynamic and reversible depending on the microenvironment.GENERAL SIGNIFICANCEOur experimental observations support the semi-independent nature of EMT-stemness connection which is very dynamic and reversible depending on the microenvironment.